2014
DOI: 10.1002/2014gl060636
|View full text |Cite
|
Sign up to set email alerts
|

GOCE's view below the ice of Antarctica: Satellite gravimetry confirms improvements in Bedmap2 bedrock knowledge

Abstract: Accurate knowledge of Antarctica's topography, bedrock, and ice sheet thickness is pivotal for climate change and geoscience research. Building on recent significant progress made in satellite gravity mapping with European Space Agency's Gravity field and Ocean Circulation Explorer (GOCE) mission, we here reverse the widely used approach of validating satellite gravity with topography and instead utilize the new GOCE gravity maps for novel evaluation of Bedmap1/2. Space-collected GOCE gravity reveals clear imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…An additional problem in Antarctica is the ice cover, which conceals the bedrock topography that gives rise to the relevant gravity anomalies. Fortunately there are now sufficient radar measurements of ice thickness to provide a reasonably accurate map of basement topography (Fretwell et al 2013), which Hirt (2014) has shown correlates with the GOCE gravity field.…”
Section: Introductionmentioning
confidence: 99%
“…An additional problem in Antarctica is the ice cover, which conceals the bedrock topography that gives rise to the relevant gravity anomalies. Fortunately there are now sufficient radar measurements of ice thickness to provide a reasonably accurate map of basement topography (Fretwell et al 2013), which Hirt (2014) has shown correlates with the GOCE gravity field.…”
Section: Introductionmentioning
confidence: 99%
“…The Bedmap2 grids substantially improve over earlier Bedmap1 data compilations over Antarctica, as is evident e.g., from independent comparisons against gravimetry (Hirt 2014). Differences in bedrock elevations between Bedmap2 and Bedmap1 are at the level of several 100 m (up to 1-2 km maximum), where new ice thickness data has become available (Fretwell et al 2013, Fig 13 ibid).…”
Section: Input Datamentioning
confidence: 70%
“…GOCE gravity gradients are used as input for many stateof-the-art gravity field models Hashemi Farahani et al 2013;Schall et al 2014;Brockmann et al 2014;, contributing significantly to those models' high accuracy and spatial resolution, with downstream applications in oceanography, geophysics and geodesy (Knudsen et al 2011;Gruber et al 2012;Fuchs et al 2013;Becker et al 2014;Hirt 2014). Beyond that, the direct use of gravity gradients in geophysical applications is currently evolving (Van der Meijde et al 2015;Bouman et al 2016).…”
Section: Introductionmentioning
confidence: 99%